Generalized Granuloma Annulare In An Actinic Distribution - Sandhu kamaldeep; Kumar A J (Wolters Kluwer Medknow Publications, 2004)
Generalized granuloma annulare is an uncommon form. Lesions localized to sunexposed areas are rare. We herein report a case of actinically distributed generalized granuloma annulare in a diabetic female.